Efeitos da alamandina em fatias hipocampais submetidas à privação de oxigênio e glicose - Beatriz Lopes Tecedor Bassi (2019)
Stroke is one of the most common vascular diseases in the world and one of the leading causes of death and disability. Existing treatments are ineffective, so studies are needed to evaluate substances that have the ability to protect the brain from the deleterious mechanisms of an ischemia. In this study, alamandine, a peptide belonging to the renin-angiotensin system (RAS), was studied and its action analyzed during ischemia and reperfusion periods in an in vitro ischemia model in hippocampal slices from C57/Bl6 male mice 8 weeks-old (N = 7 per group; CEUA / UFMG protocol No. 178/2014). The slices were first preincubated with aCSF (artificial cerebrospinal fluid) with glucose and bubbled with 95% O2 and 5% CO2 for 90 minutes. Afterward, the control group continued to receive the same condition and the ischemic group received a glucose-free aCSF, bubbled with 95% N2 and 5% CO2 aCSF for 60 minutes to mimic an ischemic event. After that, the supernatant was collected and the reperfusion time started. A dose x response curve was generated with the concentrations of 0.01nM, 0.1nM, 1nM, 10nM and 100nM of alamandine and the cell damage, glutamatergic excitotoxicity, MrgD receptor action and cell death were analyzed. All data analyzes were performed using two-way ANOVA (p<0.05). The results showed that the 1nM concentration is able to protect hippocampal slices from cellular damage when lactate dehydrogenase release was analyzed and concentrations of 1nM and 10nM were able to reduce damage by reducing glutamate release. However, in the face of MrgD receptor blockade, alamandine lost its protective action. However, when the reperfusion period was evaluated, it was not able to protect the slices from damage when evaluated the LDH release, but protection from cell death can be observed when labeled with homidimer etidium and analyzed microscopically. Overall, the results suggest that alamandine is a potential protector of cell damage and death, and further studies should be conducted of the mechanisms that occur during reperfusion.